2004
DOI: 10.1007/s00417-004-1016-6
|View full text |Cite
|
Sign up to set email alerts
|

Scleral and corneal laceration with iris prolapse caused by an eagle claw

Abstract: A bird of prey, even though caged, can injure an eye in humans. With immediate surgical treatment, good visual rehabilitation was achieved in this case. It should be reiterated that spectacles offer no protection against ocular trauma in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Common birds responsible for human injury are hens, eagles, owls, roosters, bats, ostriches, mynah, magpies, sparrows etc. [59][60][61][62][63][64][65][66][67] Most of the birds use their beaks and claws as attacking weapons. 59,68 Young children are at higher risk of bird's attack with or without provocation due to the curiosity of children to explore the living creature.…”
Section: Ocular Injury Due To Bird Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Common birds responsible for human injury are hens, eagles, owls, roosters, bats, ostriches, mynah, magpies, sparrows etc. [59][60][61][62][63][64][65][66][67] Most of the birds use their beaks and claws as attacking weapons. 59,68 Young children are at higher risk of bird's attack with or without provocation due to the curiosity of children to explore the living creature.…”
Section: Ocular Injury Due To Bird Attackmentioning
confidence: 99%
“…The literature reported that iris color, shiny cornea, and eyeball movements attract birds for attacking. 60,70 Although ocular injuries due to the pecking of birds are uncommon but sometimes could lead to severe visual impairment. 59,67,71,72 Bird peck can damage cornea, sclera, lens, and zonules.…”
Section: Ocular Injury Due To Bird Attackmentioning
confidence: 99%
“…2,3,4 However, despite of extensive search we could find only one case of ocular injury caused by eagle claw. 5 Hence we present an unusual case of penetrating ocular trauma caused by the attack of eagle claw.…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, hard beak pecking has the potential to cause severe visual function impairment [ 1 , 2 , 3 , 4 , 5 , 6 ]. Previous reports have shown that various types of birds, such as the sparrow [ 1 ], ostrich [ 2 ], rooster [ 7 ], common myna [ 3 ], crane [ 4 ], domestic hen [ 5 ], bittern [ 6 ], and eagle [ 8 ], can cause human ocular injuries, such as corneal infiltration, defects, cataract, retinal detachment, and endophthalmitis. Pecking damage is dependent on the injured site, bird size, or their attacking habit, as well as the condition of the wounds, and the clinical outcome may sometimes be poor [ 5 ].…”
Section: Introductionmentioning
confidence: 99%